PERTUMBUHAN DAN HASIL JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA KOMPOSISI MEDIA TANAM SERBUK GERGAJI AMPAS TEBU DAN KULIT PISANG YANG BERBEDA - Ayu Kurnia Putri; Titik Suryani (Universitas Sebelas Maret, 2014)
Abstract- Oyster mushroom is one of the edible mushrooms consumed by people because it contains high protein, vitamins, minerals, amino acids, low carbohydrates, fat and calories. The Content of bagasse are carbons, hydrogens,oxygens, crude proteins, crude fibers, hemicelluloses, celluloses, lignins. The content of banana peelss are water, proteins, carbohydrate, phosphorus; calcium; vitamin B and C. The Purpose of this research was to determine the growth and yield of oyster mushroom (Pleurotus ostreatus) on the different composition of sawdust, bagasse and banana peelss as the planting medium. This research is an experimental study using single factor completely randomized design consisting of five treatments: A0 (960 g sawdust, without bagasse and banana peelss), A1(930 g sawdust, 15 g bagasse and 15 g banana peelss), A2 (935 g sawdust, 15 g bagasse and 10 g banana peels), A3(920 g sawdust, 25 g bagasse and 15 g banana peelss) dan A4 (925 g sawdust, 25 g bagasse and 10 g banana peelss),3 replicates of each treatment. Data analysis used was One Way Anova test with a significance level of 0,05. The results showed that the best medium composition of 920 g sawdust, 25 g bagasse and 15 g banana peelss (A3) significantly affected the growth of oyster mushroom mycelium (29 days), the number of oyster mushroom fruit bodies (10.67 fruits at harvest I and 10.33 fruits at harvest II) and the fresh weight of oyster mushroom fruit bodies (106.67 g at harvest I and 86.67 g at harvest II). Keywords : Pleurotus ostreatus, sawdust, bagasse, banana peelss.